1967
DOI: 10.1002/jlcr.2590030502
|View full text |Cite
|
Sign up to set email alerts
|

Storage and stability of compounds labelled with radioisotopes — part II

Abstract: INTRODUCTION.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1969
1969
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…At the same time these large yields could reflect migration of energy or charge, or both, from the cellulose support material to the critical amino acids: previous studies of the modification by X-irradiation of various small molecules adsorbed on to gels indicated that there must be transfer of both electrons and protons from the gels to the adsorbed molecules (Gevantman, 1960;Allen, 1960). Such a possibility might also be consistent with the report by Bayly & Evans (1967) of the extreme lability of sugars adsorbed on to cellulose bases. By contrast, the adsorption of macromolecules on to (or into) porous substrata appears to decrease their radiation-sensitivity (Augenstein, Augenstein & Lippincott, 1960;Augenstein, 1962a;Holladay, Augenstein & Augenstein, 1966;James & Augenstein, 1966).…”
Section: P4supporting
confidence: 91%
“…At the same time these large yields could reflect migration of energy or charge, or both, from the cellulose support material to the critical amino acids: previous studies of the modification by X-irradiation of various small molecules adsorbed on to gels indicated that there must be transfer of both electrons and protons from the gels to the adsorbed molecules (Gevantman, 1960;Allen, 1960). Such a possibility might also be consistent with the report by Bayly & Evans (1967) of the extreme lability of sugars adsorbed on to cellulose bases. By contrast, the adsorption of macromolecules on to (or into) porous substrata appears to decrease their radiation-sensitivity (Augenstein, Augenstein & Lippincott, 1960;Augenstein, 1962a;Holladay, Augenstein & Augenstein, 1966;James & Augenstein, 1966).…”
Section: P4supporting
confidence: 91%
“…The stabilities of several radiolabeled alkyl halides, hydrocarbons, and cyanides are summarized in Table 1 51,52 . [ 14 C]Methyl iodide decomposes to yield a wine‐red solution (with the color resulting from the production of iodine) 73–76 .…”
Section: Self‐radiolysis Of T2omentioning
confidence: 99%
“…Self‐radiolysis is a significant challenge for radio‐chemists and has necessitated the development of several techniques to stabilize radiolabeled compounds including the addition of stabilizing agents, 32,38,39 dilution with unlabeled compound, and modification of storage conditions (storage in solution or adsorbed on paper) 40–46 . While there have been several review articles written on the subjects of 14 C and 3 H decomposition of organic compounds, 47–54 many of these articles are over 50 years old and, as such, do not include data on the decomposition of recently prepared carbon‐14 and tritium containing compounds. In this paper, a comprehensive of review of the self‐radiolysis of compounds incorporating 3 H and 14 C radiolabels is presented, and the stabilities of the radiolabeled compounds are discussed with respect of functional groups on the radiolabeled compound.…”
Section: Introductionmentioning
confidence: 99%
“…and nucleotides at high molar specific activity (above say 1 Ci/mmole) are given in the Table 2, together with estimates of their decomposition to produce radiochemical impurities (excluding THO) during one month. These estimates are based on recent results from our laboratories which are given in the Table 3, and on previously published data (18).…”
Section: Stability Of Tritiated Nucleic Acid Precursors On Storagementioning
confidence: 99%